Acute effects of energy restriction during endurance training on physical performance - Pilger, N.; Koehler, K.; Zinner, C.; Braun, H.; Mester, J.; Schaenzer, W. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Many athletes, especially participants in endurance and aesthetic sports and weight category sports, are chronically energy deficient (Loucks, 2004). The effects of energy restriction on body composition, hormone levels and metabolism are well described, but little is known about the effects on physical performance capacity. Hence, our study was aimed on the effects of energy restriction combined with endurance training on physical performance parameters. Method: Four male athletes (26 ± 3 y, 79 ± 8 kg) underwent a randomized, cross-over-design intervention. Dietary energy intake was designed to reach either a normal energy availability of 40 kcal/kg FFM (control group = CG) or a low energy availability of 15 kcal/kg FFM (energy restriction group = ERG). Each intervention went for four consecutive days and daily endurance training sessions were performed at 60% of the maximal oxygen uptake. Training energy expenditure was 15 kcal/kg FFM. Energy intake was adapted to the subjects` typical diet, which was assessed with a diet history. Pre and post tests were performed to assess body weight, body composition, submaximal cycling performance, maximal power output during a Wingate test and isometric strength tests (leg curl, leg extensions and bench press). Results: There was a significant reduction in body weight between CG and ERG of 2.5 ± 1.9 kg (p < 0.01). Body fat was reduced by 2.2 ± 1.1 kg (ERG) vs. 0.3 ± 1.1 kg (CG), without statistical significance. maximal isometric strength in bench press, leg curl and leg extension and maximal power output during the Wingate test did not change significantly. During the submaximal cycling test, heart rate was elevated during energy restriction (p < 0.05). Discussion: The results show that an acute energy restriction combined with training has no significant effects on several parameters of physical performance. Maximal anaerobic capacity measured with the Wingate test and strength tests showed no significant differences. Only in the submaximal cycling test, heart rate was significantly lower in the CG compared to ERG. If an acute energy restriction takes place in combination with training, athletes may loose weight but maximal performance capacity seems to be unaffected significantly